Second dialect acquisition - Siegel, Jeff. (Cambridge, U. K. : Cambridge University Press, 2010)
'What is involved in acquiring a new dialect - for example, when Canadian English speakers move to England or African American English-speaking children go to school? How is such learning different from second language acquisition (SLA), and why is it in some ways more difficult? These are some of the questions Jeff Siegel examines in this book, the first to focus specifically on second dialect acquisition (SDA). Siegel surveys a wide range of studies that throw light on SDA. These concern dialects of English as well as those of other languages, including Dutch, German, Greek, Norwegian, Portuguese and Spanish. He also describes the individual and linguistic factors that affect SDA, such as age, social identity and language complexity. The book discusses problems faced by students who have to acquire the standard dialect without any special teaching, and presents some educational approaches that have been successful in promoting SDA in the classroom'--
Includes bibliographical references and index.
Keywords: English language -- Variation -- English-speaking countries; English language -- Dialects -- English-speaking countries; Languages in contact -- English-speaking countries; English language -- Study and teaching; Sociolinguistics